2008
DOI: 10.1590/s1807-59322008000300001
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Output and Low Publication Rate of Brazilian Studies Presented at the American Society of Clinical Oncology Annual Meetings

Abstract: Cancer is the second most frequent cause of death, 1 with nearly half a million individuals in Brazil diagnosed with it every year.2 It has been suggested that efforts should be directed at increasing the amount of cancer research performed in Brazil, a country where the epidemiologic burden of the disease is not matched by a proportional increase in related research investments.3 Although the amount of cancer research is increasing in Brazil,4 there is a general impression that clinical research in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
1
17
0
2
Order By: Relevance
“…To our knowledge, however, there have been no previous studies on Brazilian abstracts presented at AUA Annual Meetings. We and others have shown an increasing Brazilian contribution in the areas of cardiology, neurology, oncology, and psychiatry, among others (10)(11)(12)(13). In the current study, we attempted to quantify the scientific output from Brazil in recent editions of the AUA Meetings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, however, there have been no previous studies on Brazilian abstracts presented at AUA Annual Meetings. We and others have shown an increasing Brazilian contribution in the areas of cardiology, neurology, oncology, and psychiatry, among others (10)(11)(12)(13). In the current study, we attempted to quantify the scientific output from Brazil in recent editions of the AUA Meetings.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we attempted to quantify the scientific output from Brazil in recent editions of the AUA Meetings. As a secondary goal, we aimed to compare the urological scientific output with the experience described previously in oncology, which has shown that the Brazilian contribution in this field is quantitatively increasing in a statistically significant fashion, albeit with low publication rates (13).…”
Section: Introductionmentioning
confidence: 99%
“…El comportamiento de la investigación en cáncer en Perú es similar a lo que sucede a nivel mundial, con una mayor producción en cáncer de mama (13) , pero muy pobre en otros tipos de cáncer que generan alta mortalidad, como el cáncer de próstata, pulmón e hígado (Figura 2), situación parecida a Brasil, donde hay una pobre asociación entre la carga de enfermedad por cáncer y las investigaciones realizadas (14) .…”
Section: Discussionunclassified
“…La mayoría (66,2%) de artículos se publicaron en revistas en las que el cáncer no era el tema principal (Tabla 1). La revista donde se encontró más publicaciones fue la Revista de Gastroenterología del Perú (34), seguida del Journal of Clinical Oncology (14).…”
Section: Colaboración En Investigación En Cáncerunclassified
“…Although scientific research is clearly increasing in volume in Brazil, some authors emphasize the need to enhance the conception, design, analysis, and reporting of studies that address questions relevant to our patients and our society 8,9 . Context is crucial to deciding which interventions are effective in specific populations because the effect -and therefore the impact -of some interventions could differ according to the setting 5 .…”
mentioning
confidence: 99%